Power electronics devices, circuits, and applications /: devices, circuits, and applications. ([2014]) - Rashid, Muhammad H (Muhammad Harunur), 1945-; (Professor of electrical engineering), Kumar, Narendra; Kulkarni, Ashish R (Ashish Rajeshwar)
No abstract available